Repellent effects of the essential oils of Cymbopogon citratus and Tagetes minuta on the sandfly, Phlebotomus duboscqi - Kimutai, Albert; Ngeiywa, Moses; Mulaa, Margaret; Njagi, Peter G. N.; Ingonga, Johnstone; Nyamwamu, Lydia B.; Ombati, Cyprian; Ngumbi, Philip (BMC research notes, 2017)
The sandfly, Phlebotomus duboscqi is a vector of zoonotic cutaneous leishmaniasis (ZCL) that is an important public health problem in Eastern Africa. Repellents have been used for protection of humans against vectors of ZCL and other vectors that transmit killer diseases including malaria, Rift Valley fever, dengue, and yellow fever. The repellent effects of different doses of the essential oils from the lemon grass, Cymbopogon citratus and Mexican marigold, Tagetes minuta were evaluated in a two-chamber bioassay against 3- to 7-day-old unfed females of P. duboscqi in the laboratory. The results were compared with those that were obtained when test animals were treated with an equivalent dose of diethyl-3-methylbenzamide, which is a repellent that is commonly used as a positive control. Overall, percentage repellency increased with increasing doses of the essential oils while biting rates decreased with increasing concentrations of the oils. Further, the oil of C. citratus was more potent than that of T. minuta with regard to protection time and biting deterrence. The effective doses at 50% (ED ) and at 90% (ED ) for the oil of C. citratus, were 0.04 and 0.79 mg/ml, respectively. Those of the oil of T. minuta were 0.10 and 12.58 mg/ml. In addition, the percentage repellency of 1 mg/ml of the essential oils of C. citratus and T. minuta against sandflies was 100% and 88.89%, respectively. A lower dose of 0.5 mg/ml of the oils, elicited 89.13% repellency for C. citratus and 52.22% for T. minuta. The laboratory tests showed that the essential oils of the two plants were highly repellent to adult sand flies, P. duboscqi. Thus, the two essential oils are candidate natural repellents that can be used against P. duboscqi due to their high efficacy at very low doses, hence, the envisaged safety in their use over chemical repellents. It remains to carry out clinical studies on human subjects with appropriate formulations of the oils prior to recommending their adoption for use against the sandflies.